Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - Review Exercises - Page 152: 23



Work Step by Step

3(x-2)+2x=5x-6 (left expression) 2(x+3)=2x+6 (right expression) They are equal at x=4 only. (5x-6=2x+6 implies 3x=12 which is finally x=4) The expression on the left obtained after expanding and simplifying is not equal to the expression on the right. Hence it is a conditional equation only true for some values not all.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.